Working conditions and health behavior as causes of educational inequalities in self-rated health: an inverse odds weighting approach - Schram, Jolinda LD; Oude Groeniger, Joost; Schuring, Merel; Proper, Karin I.; van Oostrom, Sandra H.; Robroek, Suzan JW; Burdorf, Alex (Scandinavian Journal of Work, Environment & Health, 2021)
' ' OBJECTIVE ': 'Using a novel mediation method that presents unbiased results even in the presence of exposure–mediator interactions, this study estimated the extent to which working conditions and health behaviors contribute to educational inequalities in self-rated health in the workforce. ' ' METHODS ': 'Respondents of the longitudinal Survey of Health, Ageing, and Retirement in Europe (SHARE) in 16 countries were selected, aged 50–64 years, in paid employment at baseline and with information on education and self-rated health (N=15 028). Education, health behaviors [including body mass index (BMI)] and working conditions were measured at baseline and self-rated health at baseline and two-year follow-up. Causal mediation analysis with inverse odds weighting was used to estimate the total effect of education on self-rated health, decomposed into a natural direct effect (NDE) and natural indirect effect (NIE). ' ' RESULTS ': 'Lower educated workers were more likely to perceive their health as poor than higher educated workers [relative risk (RR) 1.48, 95% confidence interval (CI) 1.37–1.60]. They were also more likely to have unfavorable working conditions and unhealthy behaviors, except for alcohol consumption. When all working conditions were included, the remaining NDE was RR 1.30 (95% CI 1.15–1.44). When BMI and health behaviors were included, the remaining NDE was RR 1.40 (95% CI 1.27–1.54). Working conditions explained 38% and health behaviors and BMI explained 16% of educational inequalities in health. Including all mediators explained 64% of educational inequalities in self-rated health. ' ' CONCLUSIONS ': 'Working conditions and health behaviors explain over half of the educational inequalities in self-rated health. To reduce health inequalities, improving working conditions seems to be more important than introducing health promotion programs in the workforce.
Keywords: causal mediation; educational inequality; health behavior; inverse odds weighting; longitudinal analysis; mediation analysis; self-rated health; socioeconomic inequality; working condition